2020
DOI: 10.3390/cells9071690
|View full text |Cite
|
Sign up to set email alerts
|

BE4max and AncBE4max Are Efficient in Germline Conversion of C:G to T:A Base Pairs in Zebrafish

Abstract: The ease of use and robustness of genome editing by CRISPR/Cas9 has led to successful use of gene knockout zebrafish for disease modeling. However, it still remains a challenge to precisely edit the zebrafish genome to create single-nucleotide substitutions, which account for ~60% of human disease-causing mutations. Recently developed base editing nucleases provide an excellent alternate to CRISPR/Cas9-mediated homology dependent repair for generation of zebrafish with point mutations. A new set of cytosine ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…In comparison, previous work has reported an efficiency reaching a maximum of 29% using the BE3 ( Zhang et al, 2017 ). Another more recent study employed the ancBE4max variant in zebrafish with a slight difference of efficiency that might be due to the choice of the specific locus targeted, the synthesis of the sgRNA (homemade vs commercially synthetized) and the injection mode (yolk vs cell) ( Carrington et al, 2020 ). More recently, Zhao et al, 2020 have shown similar efficiencies as we obtained in our study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, previous work has reported an efficiency reaching a maximum of 29% using the BE3 ( Zhang et al, 2017 ). Another more recent study employed the ancBE4max variant in zebrafish with a slight difference of efficiency that might be due to the choice of the specific locus targeted, the synthesis of the sgRNA (homemade vs commercially synthetized) and the injection mode (yolk vs cell) ( Carrington et al, 2020 ). More recently, Zhao et al, 2020 have shown similar efficiencies as we obtained in our study.…”
Section: Resultsmentioning
confidence: 99%
“…CBE converts C-to-T bases in a restricted window of 13–19 nucleotides (nt) upstream of the PAM sequence ( Figure 1A ). In zebrafish, a CBE was shown to work but with limited efficiencies, inducing less than 29% of gene editing and, in most cases, at least 5% of unwanted INDEL (insertion or deletion) mutations were also detected ( Carrington et al, 2020 ; Zhang et al, 2017 ). For these reasons, this editing strategy has not been so far favored by the zebrafish community.…”
Section: Introductionmentioning
confidence: 99%
“…1A). In zebrafish, a CBE has been shown to work but efficiencies were limited, with less than 29% editing being induced and, in most cases, at least 5% of unwanted INDEL (Insertion or Deletion) mutations were detected (Carrington et al, 2020;Zhang et al, 2017). For these reasons, these editing strategies have not been so far favored by the zebrafish community and no direct CBE applications have been performed to the study of developmental processes or to generate human disease models.…”
Section: Introductionmentioning
confidence: 99%
“…With slight modifications this system has been successfully used in zebrafish [ 169 ]. The CRISPR “base editing” toolkit is constantly being improved, creating new possibilities for editing [ 170 , 171 ].…”
Section: Animal Models For Drug Screening Using Genetically Encodementioning
confidence: 99%